Do we need the inherence heuristic to explain the bias towards inherent explanations?. Issue 5 (October 2014) - Dunham, Yarrow
Abstract It is clear that people often make unwarranted inherence-based explanations, but it is less clear that explaining this fact requires the inherence heuristic. Instead, it can be explained by a more general explanatory apparatus operating on the most readily available information, which, depending on the nature of that information, outputs both inherent and noninherent explanations.